Transfer of lightweight design principles from the musculoskeletal system to an engineering context. (2019) - Bartz, Marcel; Uttich, Eike; Bender, Beate
Abstract : An important source for technical lightweight design is the human musculoskeletal system. The musculoskeletal lightweight design mainly results from the coordinated interplay of different principles. Prevailing solutions that use musculoskeletal lightweight design principles neglect the coordinated interplay of these principles. Moreover, transfer is limited to isolated principles. Therefore, further potential for lightweight design can be expected. Due to the kinematic similarities of the human extremities to technical systems that can be described as open kinematic chains, in this paper the lightweight design potential is examined by applying the interaction of the aforementioned lightweight design principles to technical systems. A new bioinspired approach is developed, which implements the control and optimization running synchronously in nature in a sequential approach for technology. The bioinspired approach is implemented by coupling multibody simulation and topology optimization in an iterative process. The results of the bioinspired approach show that, compared to a classical approach, mass can be saved and deformations can be minimized. The synthesized geometry is mainly optimized for compressive stresses and therefore easier to manufacture than a bending stiff structure in the classical case. The examinations in this paper do not take application-specific requirements into account. Therefore the application to special technical systems, and furthermore advantages and disadvantages of the new approach are discussed.